Simple, but not branched, plasmodesmata allow the nonspecific trafficking of proteins in developing tobacco leaves - Imlau, Astrid; Sauer, Norbert; et al. (Cell, 1999)
Leaves undergo a sink-source transition during which a physiological change occurs from carbon import to export. In sink leaves, biolistic bombardment of plasmids encoding GFP-fusion proteins demonstrated that proteins with an M-r up to 50 kDa could move freely through plasmodesmata. During the sink-source transition, the capacity to traffic proteins decreased substantially and was accompanied by a developmental switch from simple to branched forms of plasmodesmata. inoculation of sink leaves with a movement protein-defective virus showed that virally expressed GFP, but not viral RNA, was capable of trafficking between sink cells during infection. Contrary to dogma that plasmodesmata have a size exclusion limit below 1 kDa, the data demonstrate that nonspecific "macromolecular trafficking" is a general feature of simple plasmodesmata in sink leaves.